Glycan Shielding and Modulation of Hepatitis C Virus Neutralizing Antibodies - Lavie, Muriel; Hanoulle, Xavier; Dubuisson, Jean (Frontiers in Immunology, 2018)
Hepatitis C virus (HCV) envelope glycoprotein heterodimer, E1E2, plays an essential role in virus entry and assembly. Furthermore, due to their exposure at the surface of the virion, these proteins are the major targets of anti-HCV neutralizing antibodies. Their ectodomain are heavily glycosylated with up to 5 sites on E1 and up to 11 sites on E2 modified by N-linked glycans. Thus, one third of the molecular mass of E1E2 heterodimer corresponds to glycans. Despite the high sequence variability of E1 and E2, N-glycosylation sites of these proteins are generally conserved among the seven major HCV genotypes. N-glycans have been shown to be involved in E1E2 folding and modulate different functions of the envelope glycoproteins. Indeed, site-directed mutagenesis studies have shown that specific glycans are needed for virion assembly and infectivity. They can notably affect envelope protein entry functions by modulating their affinity for HCV receptors and their fusion activity. Importantly, glycans have also been shown to play a key role in immune evasion by masking antigenic sites targeted by neutralizing antibodies. It is well known that the high mutational rate of HCV polymerase facilitates the appearance of neutralization resistant mutants, and occurrence of mutations leading to glycan shifting is one of the mechanisms used by this virus to escape host humoral immune response. As a consequence of the importance of the glycan shield for HCV immune evasion, the deletion of N-glycans also leads to an increase in E1E2 immunogenicity and can induce a more potent antibody response against HCV.